2014
DOI: 10.1099/ijs.0.058701-0
|View full text |Cite
|
Sign up to set email alerts
|

Mumia flava gen. nov., sp. nov., an actinobacterium of the family Nocardioidaceae

Abstract: Mumia flava gen. nov., sp. nov., an actinobacterium of the family Nocardioidaceae T formed a distinct clade in the family Nocardioidaceae and was most closely related to the members of the genera Nocardioides (16S rRNA gene sequence similarity, 91.9-95.1 %), Aeromicrobium (92.7-94.6 %), Marmoricola (92.5-93.1 %) and Kribbella (91.5-92.4 %). The cells of this strain were irregular coccoid to short rod shaped. The peptidoglycan contained LL-diaminopimelic acid as diagnostic diamino acid and the peptidoglycan typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…On the basis of phylogenetic, genotypic, and chemotaxonomic profiles, isolate MUSC 201 T is truly different from any existing genera in the family Nocardioidaceae ; hence, isolate MUSC 201 T represented a novel species in a new genus of the family Nocardioidaceae , for which the name “ Mumia flava gen. nov., sp. nov.” is proposed and published [55]. …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of phylogenetic, genotypic, and chemotaxonomic profiles, isolate MUSC 201 T is truly different from any existing genera in the family Nocardioidaceae ; hence, isolate MUSC 201 T represented a novel species in a new genus of the family Nocardioidaceae , for which the name “ Mumia flava gen. nov., sp. nov.” is proposed and published [55]. …”
Section: Resultsmentioning
confidence: 99%
“…This is a new genus in the family Nocardioidaceae, which was first approved in 2014 [47]. This strain was originally isolated from mangrove soil in Malaysia.…”
Section: Resultsmentioning
confidence: 99%
“…Colonies appeared after 2 weeks incubation at 25∞C. The 16S rRNA gene sequence (803 bp) of the strain was analyzed using the EzTaxon-e database (http://eztaxon-e.ezbiocloud.net/) and showed 100% similarity with that of Mumia flava MUSC 201 T (KC907394) (Lee et al, 2014). It was suggested that the strain YSP-2-79 belongs to the genus Mumia.…”
Section: Taxonomy Of the Producing Strain Of Mumiamicin (1)mentioning
confidence: 99%